TI_GERICHTE 52.2018.571 vom 24. Oktober 2018 , Licenza edilizia per la costruzione di un nuovo complesso residenziale - TI Tribunale d'appello (2018)
Licenza edilizia per la costruzione di un nuovo complesso residenziale